A study on burden among caregivers of patient with dementia in Hospital Universiti Sains Malaysia Kelantan - Tuan Zailina, Tuan Ngah (2008)
Objective Study on burden among caregivers of patient with dementia in Hospital Universiti Sains Malaysia was done to determine the degree of burden among caregivers of dementia patient and to evaluate ·the possible risk factors associated with those with higher burden. Material and Method A total of 150 of caregivers of dementia patients were interviewed. Participants were recruited from Klinik Rawatan Keluarga (KRK), Klinik Pakar Perubatan and Psychiatric clinic, HUSM. Caregiver was assessed for level of burden by Zarit Burden Interview. Caregiver was also screened for depression with PHQ-9 questionnaire. Results 69.3% of caregiver experienced mild burden, 28.0% experienced moderate burden and 2.7% experienced severe burden. 17.3% of caregivers scored 5 or more on PHQ-9 suggest of possible depression in this study. The significant association between caregiver sociodemographic characteristic and burden was caregiver level of education (p<O.OS) and caregiver responsibilities (p<0.05) with caregiver burden. Primary level of education experienced more burden than those of secondary (p<0.05) and tertiary level of X education (p<0.05). Caregiving full time and sharing care with siblings experienced more burden than those who were responsible for financial support, transport and other (p<0.05). Conclusion Factors related to caregtvers of dementia patients such as caregiver education and relationship, should be taken into account in the evaluation of caregivers' burden. Screening of depression among the caregivers is also important.